Omp35, a New Enterobacter aerogenes Porin Involved in Selective Susceptibility to Cephalosporins - Bornet, Charléric (American Society for Microbiology, 2004)
In Enterobacter aerogenes, β-lactam resistance often involves a decrease in outer membrane permeability induced by modifications of porin synthesis. In ATCC 15038 strain, we observed a different pattern of porin production associated with a variable antibiotic susceptibility. We purified Omp35, which is expressed under conditions of low osmolality and analyzed its pore-forming properties in artificial membranes. This porin was found to be an OmpF-like protein with high conductance values. It showed a noticeably higher conductance compared to Omp36 and a specific location of WNYT residues in the L3 loop. The importance of the constriction region in the porin function suggests that this organization is involved in the level of susceptibility to negative large cephalosporins such as ceftriaxone by bacteria producing the Omp35 porin subfamily.